Perancangan Aplikasi Pembelajaran Mata Pelajaran Matematika Menggunakan Model Cooperative Learning Berbasis Web (Studi Kasus : SMKN 1 Rangkasbitung) - Fauzi, Ahmad Rezki; Zakaria, Hadi (Jurnal Ilmu Komputer, 2023)
SMKN 1 Rangkasbitung is one of the vocational high schools that still applies conventional learning with teacher-centered learning patterns, so that students do not play an active role and understand the lessons given. Because the learning concept given is very difficult to understand both individually and in groups. Especially in Mathematics, where the learning model used is less varied so that the results of the Mathematics learning process are not as expected. To resolve the issue. The author uses the Cooperative Learning model in providing subject matter. It is hoped that by using this Cooperative Learning model students can play an active role, be able to understand difficult concepts and foster critical thinking and collaboration skills. So that by applying the Cooperative Learning model can help students to be more active in accepting the learning process applied by the teacher. In this implementation, the application uses the PHP programming language and data storage uses MySQL. Based on the results of the analysis of the Cooperative Learning model, it can be denied that the learning process becomes more effective and efficient, so that it makes students not feel bored in receiving learning and students can play a more active role. The material presented will also be easier for students to implement and remember with the discussion process that is carried out. In addition, researchers have also provided web-based programs to facilitate and accelerate teachers in carrying out the learning process for students because this cooperative learning model involves interaction between students in class.